ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN TERBUKA DI PROVINSI JAMBI - Jessica Dini Anjani, (2023)
Jambi Province is one of the regions in Indonesia which is rich in natural resource potential, should be able to reduce unemployment but there is still an increase in TPT which may be caused by several factors. The purpose of this research is to be able to see the influence of the variables Average Length of School (RLS), Labor Force Participation Rate (TPAK), and Gross Regional Domestic Product (GRDP) on the Open Unemployment Rate (TPT) in the Regency/City of Jambi Province. In this study, the sample used a non-probability sampling technique using a purposive sampling type in the Regency/City of Jambi Province for the 2012-2021 period. Then the number of samples used was 110 data obtained through the Jambi Provincial Statistics Center. This study uses panel data analysis, a combination of time series data and cross section data, the best model uses the Fixed Effect Model (FEM) which is developed into Feasible Generalized Least Square (FGLS). The results of the study partially show that RLS has a significant positive effect on TPT due to the low income offered by companies to prospective workers with higher education so that many are unemployed, TPAK has a significant negative effect on TPT due to an increase in the number of labor force participation which has productivity which increase economic growth thereby helping to reduce unemployment, and GRDP do not have a significant negative effect on TPT because Jambi Province has a high level of ruralization, many people are settled and looking for work so that unemployment continues to be above the target. Then the results of the study simultaneously showed that RLS, TPAK, and GRDP had an effect on TPT.